What should we focus on in pregnancy complicated by pheochromocytoma? a bibliometric analysis (1990-2024) - Deng, Shiyun; Li, Fan; Tian, Jing; Sun, Congcong; Zhang, Yanqing (Frontiers in Oncology, 2025)
Purpose of reviewThe incidence of pheochromocytoma and paraganglioma (PPGL) in pregnancy is extremely low, yet it poses a significant threat to maternal and fetal safety. While studies are published annually, progress in this field remains slow. A key question is how researchers can better utilize limited case data to gain valuable insights. This bibliometric review summarizes the current research landscape, highlights recent findings, and suggests areas for future investigations.MethodsA comprehensive search was conducted in the Web of Science Core Collection (WoSCC), PubMed, and Embase databases for PPGL in pregnancy from 1990 to 2024. Data analysis was performed using Excel 2022 and CiteSpace.Current stateA total of 391 articles were included in the analysis. The United States was the most prolific country, and the Mayo Clinic was the most productive institution. Lenders JWM was identified as both the most published and most co-cited author. Journal of the Endocrine Society was the most frequently targeted journal for publication, while the Journal of Clinical Endocrinology & Metabolism had the highest number of co-citations. Evidence-based practice in this field primarily depends on case reports, case series, case-control studies, and systematic reviews. The primary focus in this research area is on clinical management and pregnancy complications.Recent findingsMaternal and infant mortality in pheochromocytoma during pregnancy has significantly decreased due to improved awareness and advances in diagnosis and treatment. Antepartum diagnosis is the most vital element in reducing mortality; hypertension at admission and history of PPGL were independent factors of antepartum diagnosis. Abdominal/pelvic tumor location and catecholamine levels ≥10 times the upper limit of the reference range were associated with adverse outcomes. Women with hereditary disease and risk of developing PPGL should be screened before becoming pregnant for occult PPGL and should be treated adequately.ConclusionEnhanced collaboration between countries and institutions is needed to advance the field. Diagnostic and therapeutic strategies, as well as complications associated with PPGL during pregnancy, have consistently been core areas of research. Future studies should prioritize the clarification of detailed clinical management protocols and the underlying pathophysiological mechanisms, with the goal of generating high-quality evidence to guide the care of this high-risk population.